Identification of a basal system for unwinding a bacterial chromosome origin. (27th June 2019) - Richardson, Tomas T; Stevens, Daniel; Pelliciari, Simone; Harran, Omar; Sperlea, Theodor; Murray, Heath
Abstract: Genome duplication is essential for cell proliferation, and DNA synthesis is generally initiated by dedicated replication proteins at specific loci termed origins. In bacteria, the master initiator DnaA binds the chromosome origin ( oriC ) and unwinds the DNA duplex to permit helicase loading. However, despite decades of research it remained unclear how the information encoded within oriC guides DnaA‐dependent strand separation. To address this fundamental question, we took a systematic genetic approach in vivo and identified the core set of essential sequence elements within the Bacillus subtilis chromosome origin unwinding region. Using this information, we then show in vitro that the minimal replication origin sequence elements are necessary and sufficient to promote the mechanical functions of DNA duplex unwinding by DnaA. Because the basal DNA unwinding system characterized here appears to be conserved throughout the bacterial domain, this discovery provides a framework for understanding oriC architecture, activity, regulation and diversity. Synopsis: Bacterial replication origin sequences are complex and diverse. In vivo dissection of a basal bacterial chromosome unwinding mechanism in Bacillus subtilis provides a framework for understanding oriC architecture, function and diversity. A B. subtilis strain with a synthetic replication origin allows identification of a minimal set of essential sequences within B. subtilis oriC. Two DnaA‐boxes adjacent to repeating DnaA‐trios are required for DnaA‐dependent strand separation. DnaA‐dependent unwinding could be reconstituted in vitro using just these core origin sequences. DnaA filaments are guided from DnaA‐boxes onto adjacent DnaA‐trios where they stretch ssDNA to promote origin unwinding. Abstract : Systematic in vivo dissection of sequence elements essential for DnaA‐dependent strand separation in Bacillus subtilis provides a framework for understanding bacterial replication origin architecture and diversity.